Insights Chinese Primary Mathematics Teachers Gained into their Students' Learning from Using Classroom Assessment Techniques - Xiaoyan Zhao; Marja van den Heuvel-Panhuizen; Michiel Veldhuis (MDPI AG, 2019)
In this study, we explored the insights that Chinese primary mathematics teachers gained into their students’ mathematical understanding from using classroom assessment techniques (CATs). CATs are short teacher-initiated targeted assessment activities proximate to the textbook, which teachers can use in their daily practice to make informed instructional decisions. Twenty-five third-grade teachers participated in a two-week program of implementing eight CATs focusing on the multiplication of two-digit numbers, and filled in feedback forms after using the CATs. When their responses described specific information about their students, emphasized the novelty of the gained information, or referred to a fitting instructional adaptation, and these reactions went together with references to the mathematics content of the CATs, the teachers’ responses were considered as evidence of gained insights into their students’ mathematics understanding. This was the case for three-quarters of the teachers, but the number of gained insights differed. Five teachers gained insights from five or more CATs, while 14 teachers did so only from three or fewer CATs, and six teachers showed no clear evidence of new insights at all. Despite the differences in levels of gained insights, all the teachers paid more attention to descriptions of students’ performance than to possible instructional adaptations.